2011
DOI: 10.1007/jhep09(2011)134
|View full text |Cite
|
Sign up to set email alerts
|

A ten-dimensional action for non-geometric fluxes

Abstract: The NSNS Lagrangian of ten-dimensional supergravity is rewritten via a change of field variables inspired by Generalized Complex Geometry. We obtain a new metric and dilaton, together with an antisymmetric bivector field which leads to a ten-dimensional version of the non-geometric Q-flux. Given the involved global aspects of non-geometric situations, we prescribe to use this new Lagrangian, whose associated action is well-defined in some examples investigated here. This allows us to perform a standard dimensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
325
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(336 citation statements)
references
References 126 publications
11
325
0
Order By: Relevance
“…Double field theory formulations where the strong constraint is somewhat relaxed have been given for massive IIA supergravity in [29], for flux compactifications in [37,38], and explored in some generality in [39,40]. See also [41,42] for the geometric role of nongeometric fluxes in double field theory. Global aspects of double field theory are discussed in [22] where a formula for large gauge transformations was proposed and examined in detail.…”
Section: Jhep02(2014)065mentioning
confidence: 99%
“…Double field theory formulations where the strong constraint is somewhat relaxed have been given for massive IIA supergravity in [29], for flux compactifications in [37,38], and explored in some generality in [39,40]. See also [41,42] for the geometric role of nongeometric fluxes in double field theory. Global aspects of double field theory are discussed in [22] where a formula for large gauge transformations was proposed and examined in detail.…”
Section: Jhep02(2014)065mentioning
confidence: 99%
“…Following this, in [26], it was shown that the weakening of the strong constraint in the twisted reductions of DFT implies that even non-geometric gaugings of half-maximal supergravity (meaning that they cannot be T-dualized to gauged supergravities arising from conventional compactifications of ten-dimensional supergravity) has an uplift to DFT. Such non-geometric gaugings also arise from compactifications of string theory with non-geometric flux (see, for example [27][28][29]) and the relation of such compactifications with twisted compactifications of DFT was explored in various papers, including [30][31][32][33]. We should also note that, the results of [22] was also obtained by [34], by considering the duality twisted reductions of the DFT action they constructed in terms of a torsionful, flat generalized connection, called the Weitzenböck connection.…”
Section: Jhep09(2017)044mentioning
confidence: 99%
“…where F = F L ⊕ F R is the tensor sum of the left-and right-moving flux matrices and: 17) JHEP10 (2013)057 is the 2d × 2d matrix taking us from the basis (X I ,X I ) to the basis (X I L , X I R ). Explicitly, the gauge algebra takes the form:…”
Section: Jhep10(2013)057mentioning
confidence: 99%